The Neanderthal resurrection and the Abominable Snowman legend - S. Yu. Nekliudov (Шаги)
Since the 1870s, the image of the ‘prehistoric man’ has spread widely in European and American public imagination. His appearance is reconstructed by paleoanthropologists and anatomists (Schaaffhausen, Solger, Martin); under the guidance of “primitive cultures” specialists (Lubbock, Boule) it is recreated by artists (Griset, Philippart, Kupka). From the pages of illustrated magazines (Harper’s Weekly, The Illustrated London News, etc.), the ‘reconstructed’ Neanderthal gazes very much alive — hairy, long-armed, round-shouldered, with a low forehead and sunken eyes. The possibility of a direct encounter with him has been put forward by science-fiction writers (from Jules Verne to Conan Doyle and Obruchev). Such ideas could not have arisen without the influence of Darwinism; they stemmed from the understanding that various biological species that appeared at different stages of evolution coexist in living nature, including relict forms. European explorers of the Himalayas and Tibet — military men, mountaineers, naturalists of the late 19th to early 20th centuries — were readers of these magazines and books, and their worldview included a reconstructed appearance of a Neanderthal. They could easily recognize him when they met, and in that sense they were ready for such encounter. And the meeting took place: the relict hominid was discovered in the legends about the ‘Abominable Snowman’ of the Central Asian highlands. This is how hominology was born, which began to research this creature (essentially, since the 1950s) and gather information about him. Audacious, but never confirmed, paleoanthropological hypotheses have been used as a tool for interpreting local folklore texts: neither the object of research, nor the products of his vital activity, nor his remains have been found, which means that behind these texts there are only local images of ‘lower mythology’, although very specific ones.